Devaluation and its consequences in developing countries - Anne O. Krueger (Intereconomics, 1979)
To analyze the role of the trade and payments regime in economic development the National Bureau of Economic Research undertook a major research project on this issue. In this article a brief report on some of the findings pertaining to the effect of exchange rates, i. e. devaluation under exchange control is provided.
Keywords: 330; Trade Regimes